Utilização de ácido indolbutírico no enraizamento de estacas de soja - PASQUALETTO, ANTONIO; SEDIYAMA, TOCIO; SEDIYAMA, CARLOS SIGUEYUKI; ROCHA, VALTERLEY SOARES; MOSQUIM, PAULO ROBERTO (Revista Ceres, 2015)
.